Eliciting higher maximal and submaximal cardiorespiratory responses during a new taekwondo-specific aerobic test - Hausen, M.; Soares, P. P.; Araujo, M. P.; Esteves, D.; Hilbert, J.; Tauil, R.; Junca, M.; Porto, F.; Franchini, E.; Bridge, C. A.; Gurgel, J. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To propose and validate new taekwondo-specific cardiopulmonary exercise tests. Methods: Twelve male national-level taekwondo athletes (age 20 [2] y, body mass 67.5 [5.7] kg, height 175 [8] cm, and training experience 7 [3] y) performed 3 separate exercise tests in a randomized counterbalanced order: (1) a treadmill running cardiopulmonary exercise test (CPET) and (2) continuous and (3) interval taekwondo-specific cardiopulmonary exercise tests (cTKDet and iTKDet, respectively). The CPET was administered using an individualized ramp protocol. Taekwondo tests comprised sequences of turning kicks performed on a stationary target. The impacts were recorded via an electronic scoring sensor used in official competition. Stages on the cTKDet and iTKDet lasted 1 min and progressively reduced the kick interval duration. These were guided by a sound signal, starting with 4.6 s between kicks and reducing by 0.4 s every minute until the test ended. Oxygen uptake (V O2), heart rate (HR), capillary blood lactate, and ratings of perceived exertion were measured. Results: Modest differences were identified in V O2max between the tests (F2,22 = 3.54; P = .046; effect size [ES] = 0.16). Maximal HR (HRmax) was higher during both taekwondo tests (F2,22 = 14.3; P = .001; ES = 1.14) compared with CPET. Specific tests also yielded higher responses in the first ventilatory threshold V O2 (F2,22 = 6.5; P = .04; ES = 0.27) and HR (F2,22 = 12.3; P < .001; ES = 1.06), and HR at the second ventilatory threshold (F2,22 = 5.7; P = .02; ES = 0.72). Conclusions: Taekwondo-specific cardiopulmonary tests enhance the validity of some cardiopulmonary responses and might therefore be considered to optimize routine diagnostic testing and training prescription for this athletic group.